Menumbuhkan Budaya Baca Mahasiswa Melalui Program Literasi Sepuluh Menit Sebelum Perkuliahan - Muhammad Zakia Firdaus; Sukiman Sukiman (Universitas Hamzanwadi, 2020)
This study aims to describe the reading culture of students through a literacy program ten minutes before lectures. The research method used is qualitative research. Research subjects, Indonesian Language Education students in semesters one, three, and five. Collecting data to determine the reading culture of students through observation, interviews, and questionnaires. Based on the results of data collection conducted on Indonesian Language Education students, Billfath University, the following data were obtained: reading culture among sixth semester students was 58% of the total 46 students. In the third semester students the reading culture level of students is 93.75% of the total number of 20 students. The reading culture in first semester students is 65% of the total number of students 46. Thus, the literacy program ten minutes before lectures is able to foster a reading culture in students. This can be seen when the literacy program has not been implemented ten minutes before lectures. In terms of reading the most students read, namely: 65% of students read journal articles with the theme of education / teaching, 20% of students read language journal articles, and 15% of students read literary journals.